AN UNCLOUDED VIEW. Compulsory Ontology, Clinical Episteme, and Gendering Dissidence of Suicide - Stamenković, Marko (Identities: Journal for Politics, Gender and Culture, 2013)
This paper is but one part of a broader study that examines the gender-specific position of contemporary death and of suicide in particular. As a point of departure, it takes a set of arguments around discourses on suicide as hegemonic, accumulated around the sovereign domain of medical and scientific knowledge and in charge of a compulsory ontology of suicide. I understand this situation, together with Katrina Jaworski and Ian Marsh, in the first place to be highly problematic and lacking constructive counter-proposals. A major task to be undertaken is twofold: first, to scrutinize the centre of the hegemonic (clinical) episteme by penetrating its dynamics of power; then, to offer alternatives to its ‘regimes of truth’ within the plurality of epistemic models, approaches, and rationalities. To underline the extent to which the gendering process occurs therein is tantamount to this task. Accordingly, I want to argue that the dominant ontology and epistemology of suicide produce a discursively polluted and clouded backdrop where pathological and patriarchal principles still prevail. This paper thus aims at interrogating suicidology further, across its canonic strands of thought and politics of representation. Moreover, it will introduce some unexplored dissident perspectives into an existent counter-hegemonic agenda for an overall liberation from Western scientific epistemicide – the gendering of suicide being no exception to that. Author(s): Marko Stamenković Title (English): AN UNCLOUDED VIEW. Compulsory Ontology, Clinical Episteme, and Gendering Dissidence of Suicide Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 29-38 Page Count: 10 Citation (English): Marko Stamenković, “AN UNCLOUDED VIEW. Compulsory Ontology, Clinical Episteme, and Gendering Dissidence of Suicide,” Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013): 29-38.